2006
DOI: 10.1159/000092780
|View full text |Cite
|
Sign up to set email alerts
|

Higher Serum Triglyceride Level in Patients with Acute Ischemic Stroke Is Associated with Lower Infarct Volume on CT Brain Scans

Abstract: We investigated the relationship between serum triglyceride level and acute ischemic stroke severity using infarct volume on CT brain scans as a marker. A total of 121 consecutive acute ischemic stroke patients (53 males and 68 females, age 47–93 years) with anterior circulation (75%), posterior circulation (9%) or lacunar infarcts (16%) were examined. All patients were admitted within 24 h of the symptom onset, and CT scans were taken over the subsequent 24–72 h. With adjustment for the infarct type, age, sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 12 publications
4
23
0
Order By: Relevance
“…Although environmental and clinical risk factors (such as hypertension, diabetes mellitus, hyperlipemia, atherosclerosis, smoking, excessive alcohol drinking, and so on) are considered important [3,4], nowadays a growing spectrum of genetic susceptibility factors have been identified [5,6]. With the help of robust genome-wide association studies, the biological plausibility and epidemiological evidence suggest that the elevated triglyceride (TG) level potentially contributes to an increased risk for ischemic stroke [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Although environmental and clinical risk factors (such as hypertension, diabetes mellitus, hyperlipemia, atherosclerosis, smoking, excessive alcohol drinking, and so on) are considered important [3,4], nowadays a growing spectrum of genetic susceptibility factors have been identified [5,6]. With the help of robust genome-wide association studies, the biological plausibility and epidemiological evidence suggest that the elevated triglyceride (TG) level potentially contributes to an increased risk for ischemic stroke [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…While several observational studies have not found any consistent association between prestroke total cholesterol (TC) levels and stroke mortality, [18] post-stroke levels of TC seem to have a negative association with stroke mortality and prognosis [8,24]. Moreover, low serum triglyceride (TG) levels have been associated with increased mortality after an ischemic stroke (IS) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown patients with serum triglyceride levels below 150 mg/dL on admission after acute stroke are associated with stroke severity and worse prognosis [6][7][8][9][10][11][12][13]17]. A retrospectively study found a higher serum triglyceride level (≥ 150 mg/dL) within 24 h after admission is associated with a lower infarct volume on CT brain scans [6]. Dziedzic et al [7] have shown that a higher level of serum triglyceride (>2.3 mmol/L) is associated with 42% reduced stroke severity [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies also found that low serum triglyceride levels measured in the early period after stroke are predictive of higher infarct volume [6], more severity [7,8], and both elevated short-term mortality and long-term mortality [9][10][11][12][13]. On the other hand, a Korean study found a J-shape relation between triglyceride levels and early neurological deterioration and mortality [14].…”
Section: Introductionmentioning
confidence: 99%